Ketone Bodies Inhibit the Opening of Acid-Sensing Ion Channels (ASICs) in Rat Hippocampal Excitatory Neurons in vitro - Zhu, Fei; Shan, Wei; Xu, Qinlan; Guo, Anchen; Wu, Jianping; Wang, Qun (Frontiers in Neurology, 2019)
Objectives: Despite the long-term efficacy of antiepileptic drug treatments, frequent attacks of drug-resistant epilepsy necessitate the development of new antiepileptic drug therapy targets. The ketogenic diet is a high-fat, low-carbohydrate diet that has been shown to be effective in treating drug-resistant epilepsy, although the mechanism is yet unclear. In the ketogenic diet, excess fat is metabolized into ketone bodies (including acetoacetic acid, β-hydroxybutyric acid, and acetone). The present study explored the effect of ketone bodies on acid-sensing ion channels and provided a theoretical basis for the study of new targets of antiepileptic drugs based on” ketone body-acid sensing ion channels.” Methods: In this study, rat primary cultured hippocampal neurons were used. The effects of acetoacetic acid, β-hydroxybutyric acid, and acetone on the open state of acid-sensing ion channels of hippocampal neurons were investigated by the patch-clamp technique. Results: At pH 6.0, the addition of acetoacetic acid, β-hydroxybutyric acid, and acetone in the extracellular solution markedly weakened the currents of acid-sensing ion channels. The three ketone bodies significantly inhibited the opening of the acid-sensing ion channels on the surface of the hippocampal neurons, and 92%, 47%, and 77%, respectively. Conclusions: Ketone bodies significantly inhibit the opening of acid-sensing ion channels. However, a new target for antiepileptic drugs on acid-sensing ion channels is yet to be investigated.